Development of a Holistic Parent’s Guide for the Pancasila Student Profile Strengthening Project During the Transition from Early Childhood Education to Elementary School - Agustini, Agustini; Djafri, Novianty (PPSDP International Journal of Education, 2024)
This study aimed to provide parents with a deeper understanding of the transition from Early Childhood Education to elementary school within the framework of the Pancasila Student Profile Strengthening Project (P5). The study employed a Research and Development approach using the Dick and Carey model to develop the product. Data were collected through interviews, document analysis, questionnaires, and assessments of the achievement of the Pancasila student profile. The population of this study consisted of parents of Kindergarten B students from Al Ishlah Kindergarten, Asmaul Husna Kindergarten, and Lukmanul Hakim Kindergarten in Gorontalo City, Gorontalo Province. A sample of 10 parents was selected for the limited field test. For the large-scale field test, samples were taken from two different schools: Al Ishlah Kindergarten, Asmaul Husna Kindergarten, and Lukmanul Hakim Kindergarten, with 20 parents from each school. The results showed that the Parent’s Guide for the transition from PAUD to elementary school was deemed suitable and of high quality, and can be used by parents to strengthen the P5 during the transition.